International Trade Relations of Turkey and South Africa: A Historical Perspective - Bisharo Ali Mohamud; Cihat Koksal (Journal of International Trade, Logistics and Law, 2021)
South Africa attracted the attention of the world with its rich natural resources such as gold and diamonds, followed a closed foreign trade policy until the end of the apartheid period in the 1990s. With the transition to democracy, South Africa launched a forward-looking and comprehensive economic development by becoming a member of organizations like the World Trade Organization (WTO) and BRICS. Moreover, international trade policies and financial transactions have been liberalized and simplified. In the early 2000s, Turkey began to build and develop its relationships overseas, such as with African Countries. Turkey has a long tradition of involvement in Africa. The aim of this study is to analyze the international trade relations between Turkey and Africa particularly South Africa from a historical perspective. The results conclude important policy recommendations for increasing the trade potential of the two countries under investigation.